Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Lithium compound catalyzed deoxygenative hydroboration of primary, secondary and tertiary amides - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2021)
A selective and efficient route for the deoxygenative reduction of primary to tertiary amides to corresponding amines has been achieved with pinacolborane (HBpin) using simple and readily accessible 2,6-di-tert-butyl phenolate lithium center dot THF (1a) as a catalyst. Both experimental and DFT studies provide mechanistic insight.

Readily available lithium compounds as catalysts for the hydroboration of carbodiimides and esters - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Journal of Organometallic Chemistry, 2021)
Selective and efficient hydroboration of esters and carbodiimides to alcohols and amines by two welldefined and readily accessible lithium complexes, 2,6-di-tert-butyl phenolate lithium (1a ) and 1,1'-dilithioferrocene (1b ) are described. A range of aliphatic, aromatic, and cyclic esters with various functional groups were selectively converted into the corresponding boronate esters. Similarly, the single hydroboration of carbodiimides with aliphatic and aromatic substituents on the nitrogen atoms was studied. A possible mechanistic pathway of the hydroboration of carbodiimides with HBpin has been proposed using NMR studies and DFT calculations. These reactions are convenient alternatives to stoichiometric hydride reduction or hydrogenation. The employing of lithium complexes is also significant, because of the need to find cheap and green alternatives to noble metal complexes. (C) 2021 Elsevier B.V. All rights reserved.

Hypersilyl substituent in heavier low-valent group 14 chemistry - Gour, Kritika; Bisai, Milan Kumar; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2022)
The isolation of unusual compounds with low-valent main-group elements would not have been possible without the development of a series of sterically demanding ligands with bulky substituents. While early literature recognizes the advent of the sterically demanding tris(trimethylsilyl)silyl (SiMe3)(3)Si- group, also known as hypersilyl group, to stabilize species with new coordination modes for the main group elements, it has largely been more recent studies that have utilized this group for isolating stable compounds with low-valent main-group elements. Such compounds are not only interesting from the structure-bonding point of view but showcase potential for small molecule activation under ambient conditions. This review will cover the recent developments in stabilizing unusual compounds with group 14 elements using the exceptionally strong sigma-donor properties and pronounced steric effects of the hypersilyl moiety, emphasizing their synthesis, structure, and reactivity.
Keywords: Germylenes; Hydroboration; Hypersilyl; silylenes; Stannylenes

Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling